2017
DOI: 10.1093/sleep/zsx184
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of Apnea by Cannabimimetic Enhancement, the PACE Clinical Trial: Effects of Dronabinol in Obstructive Sleep Apnea

Abstract: These findings support the therapeutic potential of cannabinoids in people with OSA. In comparison to placebo, dronabinol was associated with lower AHI, improved self-reported sleepiness, and greater overall treatment satisfaction. Larger scale clinical trials will be necessary to clarify the best potential approach(es) to cannabinoid therapy in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 32 publications
0
60
0
4
Order By: Relevance
“…Although undiluted DMSO alone did not alter apnea expression in these studies [4,8], DMSO may have altered the effects of dronabinol, since it is known to block fast axonal transport in the vagus nerve. Still, it is important to note that dronabinol dissolved in sesame oil rather than DMSO 9 did reduce apnea frequency in two clinical trials in patients with obstructive sleep apnea syndrome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although undiluted DMSO alone did not alter apnea expression in these studies [4,8], DMSO may have altered the effects of dronabinol, since it is known to block fast axonal transport in the vagus nerve. Still, it is important to note that dronabinol dissolved in sesame oil rather than DMSO 9 did reduce apnea frequency in two clinical trials in patients with obstructive sleep apnea syndrome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…5 This led to human studies that assessed the effectiveness of dronabinol in pill form of different strengths from 2.5 to 10 mg to treat patients with OSA. [6][7][8] Prasad et al reported a significant improvement in apneahypopnea index (AHI) of 32% at 3 weeks compared to baseline (−14.1 ± 17.5; P = .007). Side effects related to treatment were reported in most patients, and somnolence was reported in 29% to 50% of patients.…”
Section: Canna Bi S and Sleepmentioning
confidence: 99%
“…Eight percent of patients reported sleepiness and drowsiness. 8 Importantly, the long-term use of these products on other sleep quality measures, their tolerability, and safety are still unknown. Dronabinol is not FDA approved for treatment of OSA.…”
Section: Canna Bi S and Sleepmentioning
confidence: 99%
“…The results of the recent pharmacotherapy of apnea by cannabimimetic enhancement (PACE) trial that studied the effects of dronabinol (a cannabinoid) on the effects of obstructive sleep apnea look promising. 1 In light of this study and the upcoming legalization of marijuana in Canada, could the authors of the recent CMAJ review 2 on the diagnosis and treatment of obstructive sleep apnea in adults please comment on the use of marijuana and its pharmacologic derivatives in the treatment of obstructive sleep apnea?…”
Section: Medical Marijuana In Treating Obstructive Sleep Apneamentioning
confidence: 99%